Application of Agile Approach in Transportation Management System Development to Improve Construction Company Performance - Sihombing, Denny Jean Cross (Jurnal Ekonomi, 2024)
This research aims to explore the application of an Agile approach in developing a transport management system to improve the performance of construction companies. Problems encountered in construction transport management, including inflexibility, non-adaptability, and lack of communication, prompt a more dynamic and responsive approach. This research method involves stages of system development, from requirements definition to testing, by applying Agile principles such as Scrum or Kanban. Through thorough testing, the system is confirmed to have met the set quality standards before being widely implemented. The results show that applying Agile approaches can provide the flexibility, adaptability, and responsiveness needed to deal with the complexities in construction transport management. The contribution of this research is that it provides valuable insights for practitioners and academics in understanding the potential of Agile approaches in improving efficiency, transparency, and risk management in construction projects, as well as offering a foundation for developing more effective transport management systems in the future.